2012
DOI: 10.1103/physrevb.86.054433
|View full text |Cite
|
Sign up to set email alerts
|

Signature of an antiferromagnetic metallic ground state in heavily electron-doped Sr2FeMoO6

Abstract: Sr2FeMoO6 is a well-known double perovskite with exciting high-temperature magnetic properties. Through various magnetic and spectroscopic measurements, we collect compelling evidence here that this compound can be driven into a rare three-dimensional antiferromagnetic metallic state by heavy electron doping (70% Sr2+ substitution by La3+). Moreover, local structural study of these Sr2-xLaxFeMoO6 (1.0 <= x <= 1.5) compounds reveals unusual atomic scale phase distribution in terms of La,Fe- and Sr,Mo-rich regio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Interesting enough, the hybridization-driven mechanism supports filling driven FM-AFM transition, which was predicted theoretically 30 and verified experimentally 31 for La-doped Sr 2 Fe-MoO 6 . As opposed to super-exchange driven insulating AFM state found in DPs, 32 the AFM phase within the hybridization-driven mechanism of magnetism is metallic.…”
Section: Mechanism Of Magnetism and Model Calculation Of Magnetic Trasupporting
confidence: 67%
“…Interesting enough, the hybridization-driven mechanism supports filling driven FM-AFM transition, which was predicted theoretically 30 and verified experimentally 31 for La-doped Sr 2 Fe-MoO 6 . As opposed to super-exchange driven insulating AFM state found in DPs, 32 the AFM phase within the hybridization-driven mechanism of magnetism is metallic.…”
Section: Mechanism Of Magnetism and Model Calculation Of Magnetic Trasupporting
confidence: 67%
“…Based on this understanding, tailoring of their magnetic/electronic properties have been proposed, which resulted in prediction of antiferromagnetic metallic state in La doped Sr 2 FeMoO 6 [11] and prediction of halfmetallic ferromagnetic with high T c in Na and La doped Sr 2 CrOsO 6 [12]. While the former computational prediction has been verified experimentally [32], the later is yet to be taken up by the experimentalists.…”
Section: Discussionmentioning
confidence: 99%
“…(La/Sr) 3 Mn 2 O 7 or Ca 3 Ru 2 O 7 [30], and only one in case of three-dimensional transition metal oxide, namely CaCrO 3 [31]. The prediction [11] of doping driven transition from ferromagnetic to antiferromagnetic metallic state in La doped Sr 2 FeMoO 6 , which subsequently have been confirmed experimentally through magnetic and spectroscopic measurements, therefore was unexpected [32]. A combination of first-principles density functional calculation and exact diagonalization of low-energy Fe-Mo model Hamiltonian was used to explore the effect of La doping in Sr 2 FeMoO 6 [11].…”
Section: Curious Case Of Antiferromagnetic Metallic Double Perovskitesmentioning
confidence: 93%
“…However, recent investigation has shown that the ferromagnetic state of La x -Sr 2Àx FeMoO 6 becomes unstable, and the T C will decrease when too many electrons are doped in the conduction band (x > 1). [28][29][30] These are representative examples displaying a strong dependence of the physical property on the carrier number in A 2 FeMoO 6 (A: Ca/Ba/Sr) systems. Except for the T C , other physical properties, such as the chemical states of Fe and Mo ions, magnetization, resistivity behavior, and the MR performance, are greatly inuenced by the carrier density as well.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the T C , other physical properties, such as the chemical states of Fe and Mo ions, magnetization, resistivity behavior, and the MR performance, are greatly inuenced by the carrier density as well. 15,17,19,21,23,28,[31][32][33][34] Hence, the concept of carrier density at the Fermi level is important for understanding and manipulating the physical properties in SFMO. To understand the effect of carrier density on the physical properties of SFMO, it is important to articially control the carrier density in SFMO ceramics using an experimental strategy.…”
Section: Introductionmentioning
confidence: 99%